Rancang Bangun Alat Ukur Ankle Brachial Indeks Untuk Deteksi Peripheral Artery Disease - Rika Wahyuni Arsianti; Sardina Sardina; Fairul Fairul; Irfan Irfan; Mulyadi Mulyadi (Universitas Syiah Kuala, 2020)
Abstract—ABI measurements are performed to detect PAD. ABI measurements are essential because, generally, patients are not aware of having PAD due to no significant signs and symptoms. Type 2 Diabetes Mellitus Patients tend to have PAD, which increases the risk of cardiovascular and mortality. Therefore, the measurement of ABI regularly is needed to prevent PAD. Early detection and regular monitoring of PAD by measuring ABI can avoid foot complications, such as injuries, gangrene, and amputation. The standard method to measure ABI is using Doppler. Unfortunately, not all health care providers have Doppler because it is an expensive instrument and relatively difficult to use. The purpose of this study is to design a simple and easy Prototype to measure ABI by using pressure sensors. Two pressure sensors measure the systole of blood pressure in the arm and leg to get the ABI. This study’s sample is 20 people consisting of 10 healthy people and ten diabetes mellitus patients. The result shows the ABI prototype has an error of 0.53% with an accuracy rate of 99.47%. It is indicated that the ABI prototype can be used for diagnosing PAD.